Exposure time and ventricular remodeling induced by tobacco smoke exposure in rats - Castardeli, Edson [UNESP]; Duarte, Daniella R. [UNESP]; Minicucci, Marcos F. [UNESP]; Azevedo, Paula S. [UNESP]; Matsubara, Beatriz B. [UNESP]; Matsubara, Luiz S. [UNESP]; Campana, Álvaro O. [UNESP]; Paiva, Sergio A. R. [UNESP]; Zornoff, Leonardo A. M. [UNESP] (My University, 2008)
Background: We investigated the effects of length of exposure to tobacco smoke on the cardiac remodeling process induced by exposure to cigarette smoke in rats. Material/Methods: Rats were separated into 4 groups: nonsmoking (NS)2 (n=25; control animals not exposed to tobacco smoke for 2 months), smoking (S)2 (n=22; rats exposed to smoke from 40 cigarettes/d for 2 months), NS6 (n=18; control animals not exposed to tobacco smoke for 6 months), and S6 (n=25; rats exposed to smoke from 40 cigarettes/d for 6 months). All animals underwent echocardiographic, isolated heart, and morphometric studies. Data were analyzed with a 2-way analysis of variance. Results: No interaction among the variables was found; this suggests that length of exposure to tobacco smoke did not influence the effects of exposure to smoke. Values for left ventricular diastolic diameter/body weight and left atrium/body weight were higher (p=0.023 and p=0.001, respectively) in smoking (S2 and S6) than in nonsmoking animals (NS2 and NS6). Left ventricular mass index was higher (p=0.048) in smoking than in nonsmoking animals. In the isovolumetrically beating ventricle, peak systolic pressure was higher (p=0.034) in smoking than in nonsmoking animals. Significantly higher values were found for left ventricular weight (p=0.017) and right ventricular weight (p=0.001) adjusted for body weight in smoking as opposed to nonsmoking animals. Systolic pressure was higher (p=0.001) in smoking (128±14 mm Hg) than in nonsmoking animals (112±11 mm Hg). Conclusions: Length of exposure to cigarette smoke did not influence cardiac remodeling caused by exposure to smoke in rats. © Med Sci Monit, 2008.
Keywords: Fibrosis; Ventricular dilatation; Ventricular function